The Irishman [videorecording (DVD)] - Pacino, Al, 1940-; Pesci, Joe; Romano, Ray; Cannavale, Bobby; Paquin, Anna; Brandt, Charles (Criterion collection, 2020)
An epic saga of organized crime in post-war America told through the eyes of World War II veteran Frank Sheeran, a hustler and hitman who worked alongside some of the most notorious figures of the twentieth century. Left behind by the world, former hit man and union truck driver Frank Sheeran looks back from a nursing home on his life's journey through the ranks of organized crime: from his involvement with Philadelphia mob boss Russell Bufalino to his association with Teamsters union head Jimmy Hoffa to the rift that forced him to choose between the two.